Synthesis of amino acid functionalized Fe3O4 nanoparticles for adsorptive removal of Rhodamine B - Neway Belachew; Aschalew Tadesse; Mebrahtu Hagos Kahsay; Desta Shumuye Meshesha; Keloth Basavaiah (Applied Water Science, 2021)
Abstract L-Aspartic acid (L-Asp) functionalized magnetite nanoparticles (Fe3O4 NPs) were synthesized through a facile co-precipitation method using L-Asp as a capping agent. UV–Vis, FTIR, XRD, SEM, EDS, TEM, and VSM techniques were used to investigate the formation, morphology, elemental composition, and magnetic properties of the synthesized Fe3O4 NPs. Highly crystalline and spherical shaped pure phase Fe3O4 NPs were successfully synthesized using amino acid as a capping agent. The magnetic measurement analysis confirms the superparamagnetic nature of the synthesized L-Asp capped Fe3O4 NPs. The adsorption efficiency of L-Asp capped Fe3O4 NPs was assessed by the removal of Rhodamine B (RhB). The optimum removal efficiency was found to be 7.7 mg g−1 using 1 mg mL−1 adsorbent, and 30 mg L−1 RhB at pH 7 and 25 °C. The regression (R 2 adj) and standard deviation (SD) analysis were used to validate both kinetic and isotherm models. Avrami fractional-order and Liu models were selected as the best kinetic and isotherms, respectively. The maximum adsorption capacity (Q o) of L-Asp Fe3O4 NPs toward RhB Liu’s model was found to be 10.44 mg g−1.